Estradiol valerate plus dienogest versus ethinylestradiol plus levonorgestrel for the treatment of primary dysmenorrhea. Issue 3 (11th March 2014) - Petraglia, Felice; Parke, Susanne; Serrani, Marco; Mellinger, Uwe; Römer, Thomas
Abstract: Objective: To demonstrate the superiority of estradiol valerate plus dienogest (E2 V/DNG) over ethinylestradiol plus levonorgestrel (EE/LNG) in reducing the number of days with dysmenorrheic pain among women with primary dysmenorrhea. Methods: In a phase IIIb trial conducted at 44 centers worldwide between April 2009 and November 2010, otherwise healthy women aged 14 − 50 years requesting contraception were randomized to daily oral administration of E2 V/DNG (n = 253) or EE/LNG (n = 254) for three 28‐day cycles. The primary efficacy variable was number of days with dysmenorrheic pain, the category of which (none, mild, moderate, severe) was self‐assessed on a daily basis (irrespective of menstrual bleeding status) and recorded on diary cards. Notably, the women documented their pain as they experienced it before taking any (permitted) rescue medication. Results: Overall, 217 and 209 women receiving E2 V/DNG and EE/LNG, respectively, completed the study. The mean ± SD change from baseline in number of days with dysmenorrheic pain was −4.6 ± 4.6 days and −4.2 ± 4.2 days for the E2 V/DNG and EE/LNG groups, respectively ( P = 0.34). Conclusion: Both E2 V/DNG and EE/LNG led to considerable relief of dysmenorrheic complaints among women with primary dysmenorrhea, decreasing the number of days with dysmenorrheic pain from baseline to a similar extent. ClinicalTrials.gov :NCT00909857